"I'm here for recovery": the eudaimonic wellness experiences at the Le Monastère des Augustines Wellness hotel. Issue 8 (13th October 2021) - Kim, Bona; Yang, xiaotao
ABSTRACT: This study uses Le Monastère des Augustines Wellness Hotel to explore healing seekers' eudaimonic wellness experiences and how such experiences are conceptualized in alignment with their underlying transformative process in a restorative environment. Using participant observation, secondary data, and thirteen in-depth interviews with eight participants, four key elements regarding wellness hotel experience were identified: 1) the museum and its inspiring reflections; 2) the historical facilities and the power of quietness; 3) the wellness lifestyle and its lasting impacts; and 4) the religious encounters, caring staff, and feeling of being cared for. We further construct a four-stage transformative process of wellness experience: realization, involvement, transformation and appreciation.